Determination of sustainable food land directions in Bantul Regency, Indonesia based on food security level and land use conversion - Hanifah Mahat (Tanjung Malim, 2023)
Determination of sustainable food land directions in Bantul Regency, Indonesia based on food security level and land use conversion by Hanifah Mahat